Children's understanding of basic number concept. - Gordon, Lisa Lande. (The University of Arizona., 1994)
Three experiments were completed in this study in order to explore gist/verbatim independence/dependence. The first experiment was interested in developmental differences in verbatim memory performance, while the second and third experiments were concerned with developmental differences in verbatim memory and in relationships between verbatim and separate forms of gist memories. Extant data have demonstrated that accurate performance on reasoning tasks does not rely on accurate verbatim memory. However, how separate gists interact with each other, and each in relation to verbatim memory, has previously received scant attention. Results from Experiments 2 and 3 revealed stochastic independence between gists, and between separate gists and verbatim memory. In addition, distinct developmental patterns were uncovered. Younger subjects appear to have performed most accurately on nominal gist, while second grade subjects performed worst on nominal probes. Similarly, second graders responded most accurately on relational probes, while preschoolers performed poorest on relational probes. Additionally, consistent with recent literature on memory development that finds verbatim-reasoning independence, verbatim probes were not found to yield the highest rate of accuracy. If performance accuracy on reasoning tasks was dependent on accurate verbatim encoding, memory would have been better for verbatim information than for both relational and nominal. Experiment 3 explored the effects of training on gist extraction. Although training was not found to generate a statistically significant difference in performance for either age relative to the control groups' performance, indirect support for its impact on performance was found, and reviewed. Relative to those in the control group, the preschoolers in the experimental group seemed to benefit from training and demonstrated a performance pattern comparable to that of the second graders', although significance was not determined in these experiments. In summary, clear evidence of verbatim-gist independence was found, and indicates that separate gists may also function as distinct and individual processes. Additionally, there was some indication that training may elicit comparable gist performance patterns between age-groups, but the subject pool in these experiments appears to have been too small to exploit a training impact.